The Effect of a One-Session Archery Qualification Round on Body Fluid Loss among University Archery Athletes - Nurikhwan Aziz Arifin; Ikroom Pranajaya; Masyita Siregar (Gladi : Jurnal Ilmu Keolahragaan, 2026)
This study aims to determine the effect of archery sports activities on decreasing body fluid levels among members of the Archery Achievement Sports Club (KOP) at Universitas Negeri Jakarta. The research was conducted in one day and one session at the archery field of Campus B, Universitas Negeri Jakarta. This study used a pre-experimental method with a one-group pretest–posttest design. The sampling technique applied was purposive sampling, involving 11 participants selected from a total population of 16 members based on predetermined inclusion criteria. Body fluid loss was measured before and after participants completed an archery activity using a one-session qualification round method. The data were analyzed using a dependent t-test. The results showed that the average decrease in body fluid level was 390.9 ml, with a standard deviation of 7.348 and a standard error of 2.325. The statistical analysis obtained a t-value of 168.491, which was higher than the t-table value of 1.812 at a significance level of 5%. These findings indicate that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. Therefore, it can be concluded that archery sports activities significantly affect the decrease in body fluid levels among members of the Archery Achievement Sports Club (KOP) at Universitas Negeri Jakarta